Rapid Plasmid-Mediated Acquisition of Erythromycin Resistance via ermX in Corynebacterium striatum: A 72-Hour Clinical Evolution - Chen Z; Jiang Y; Wang D; Jiang S (Infection and Drug Resistance)
Zongyao Chen,1,2 Yayun Jiang,1,2 Dengchao Wang,1,2 Shuming Jiang3 1Department of Clinical Laboratory, People’s Hospital of Deyang City, Deyang, People’s Republic of China; 2Pathogenic Microbiology and Clinical Immunology Key Laboratory of Deyang City, Deyang, People’s Republic of China; 3Pathology Department, People’s Hospital of Deyang City, Deyang, People’s Republic of ChinaCorrespondence: Shuming Jiang, Pathology Department, People’s Hospital of Deyang City, Deyang, People’s Republic of China, Email jiangsm211@163.comPurpose: To investigate the genomic mechanisms driving rapid erythromycin resistance emergence in Corynebacterium striatum during clinical management of urinary tract infections.Methods: Longitudinal analysis of four C. striatum isolates (C1-C4) from an ICU patient with candida coinfection was conducted using CLSI M45-A3-guided microbroth dilution and comparative whole-genome sequencing. Phylogenetic reconstruction (27 housekeeping genes) confirmed clonal origin, while CARD/PIPdb/ISfinder databases characterized resistome dynamics.Results: Erythromycin susceptibility shifted from susceptible (minimum inhibitory concentration, MIC ≤ 0.25 μg/mL) to resistant (MIC = 4 μg/mL) within 72 hours, correlating with acquisition of a plasmid carrying ermX flanked by ISL3-family elements (ISCx1).Conclusion: This first documentation of sub-72-hour ermX plasmid acquisition in C. striatum highlights critical infection control challenges in ICU settings. We recommend daily antimicrobial susceptibility testing (AST) profiling for C. striatum in ICU patients receiving macrolides, coupled with PCR screening for ermX to preempt resistance dissemination.Keywords: Corynebacterium striatum, erythromycin, ermX, whole genome sequencing, resistance